Pelajau Kaul and the Sambas Connection - Ann, Appleton (Universiti Malaysia Sarawak (UNIMAS), 2011)
A link between Sambas and the Melanau communities on the Oya River has been recognized for many years. However, the details of the connection have remained relatively muted in the historic and ethnographic record. Drawing on recent ethnographic fieldwork with Melanau communities on the Oya River - including the collection of oral history narratives and family genealogies, this paper traces the history of the Sambas-Oya River connection and explores its relevance to Melanau identity and social organization on the Oya River in the present day. Further, it argues that this connection is collectively reaffirmed and revitalized on the 29th of December each year when descendants of a former longhouse community at Pelajau, forty miles upriver from the Sarawak coast, return to the long abandoned site to celebrate Pe1ajau Kaul.